Occurrence and Health Risk of Patulin and Pyrethroids in Fruit Juices Consumed in Bangkok, Thailand - Poapolathep, Saranya; Tanhan, Phanwimol; Piasai, Onuma; Imsilp, Kanjana; Hajslova, Jana; Giorgi, Mario; Kumagai, Susumu; Poapolathep, Amnart (Journal of food protection, 2017)
The mycotoxin patulin (PAT) is well known as a natural contaminant of apple- and other fruit-based products. Pesticides are a group of chemicals abundantly used in agriculture to maximize productivity by protecting crops from pests and weeds. Because of their harmful health effects, PAT and pesticides are strictly monitored. The current study was undertaken to investigate the significance of PAT and pyrethroid insecticide contamination in a variety of fruit juices in Bangkok. To do this, a total of 200 fruit juice samples, consisting of 40 samples each of apple, apricot, peach, pineapple, and grape juice, were collected from supermarkets in Bangkok, Thailand. PAT contamination in a variety of fruit juices was detected using validated liquid chromatography-tandem mass spectrometry, and pyrethroid insecticides (cypermethrin, cyfluthrin, and flumethrin) were analyzed using a gas chromatography equipped with micro-electron capture detector. The survey found that PAT concentrations were lower than the maximum residue limit established by European Union. The results of the present study suggest that the risk of exposure to harmful levels of PAT, cypermethrin, cyfluthrin, and flumethrin in fruit juices is very low in urban areas of Thailand.
Keywords: Beverages; Fruit and Vegetable Juices; Malus; nápoje; pyrethriny; Food Contamination; Pyrethrins; patulin; Thajsko; Patulin; Thailand; ovoce; kontaminace potravin; ovocné a zeleninové šťávy; Fruit